2017
DOI: 10.1002/ijgo.12361
|View full text |Cite
|
Sign up to set email alerts
|

Maternal morbidity after implementation of a postpartum hemorrhage protocol including use of misoprostol

Abstract: Implementation of the PPH protocol decreased rates of postpartum anemia and postpartum hysterectomy owing to uterine atony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(64 reference statements)
3
4
0
Order By: Relevance
“…In order to further elucidate the downstream mechanism of miR‐132 in regulating macrophage differentiation, we found that miR‐132 could target Mycbp2. Mycbp2 is an inhibitor of the M2 macrophage polarization, which executes its suppressive effect via various signalling pathway 36 . In addition to that, we also found that overexpression of Mycbp2 reversed the effects of overexpressed miR‐132 on M2 polarization of macrophages, indicating that miR‐132 can target Mycbp2 in macrophages to promote M2 polarization of macrophages.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In order to further elucidate the downstream mechanism of miR‐132 in regulating macrophage differentiation, we found that miR‐132 could target Mycbp2. Mycbp2 is an inhibitor of the M2 macrophage polarization, which executes its suppressive effect via various signalling pathway 36 . In addition to that, we also found that overexpression of Mycbp2 reversed the effects of overexpressed miR‐132 on M2 polarization of macrophages, indicating that miR‐132 can target Mycbp2 in macrophages to promote M2 polarization of macrophages.…”
Section: Discussionsupporting
confidence: 71%
“…Mycbp2 is an inhibitor of the M2 macrophage polarization, which executes its suppressive effect via various signalling pathway. 36 In addition to that, we also found that overex- Translation processes are modulated by Mycbp2 mainly through the mTOR signalling where Mycbp2 has a double function by ubiquitylating the Rheb inhibitor TSC2. 37 As reported, TSC1/2 complex inhibits the Ras GTPase pathway to restrict M1 response, and its vital role in M2 activation is basically regulated by suppressing the mTOR pathway.…”
Section: Discussionsupporting
confidence: 57%
“…It is impossible to know if the results observed in these studies were causally linked to the drafting of local clinical guidelines, as their intervention also included theoretical and training sessions [ 15 ]. As in our work, the single-center studies observed lower maternal morbidity [ 29 , 30 ]. In our study, unlike that by Shields et al [ 22 ], blood transfusions were less frequent among the category 1 maternity units.…”
Section: Discussionsupporting
confidence: 82%
“…The association between preeclampsia and postpartum hemorrhage has been shown in various studies [ 5 ]. Studies show that careful use of clinical protocols to control PPH not only prevents uterine atony and improves the conditions of preeclamptic women, but also it prevents dangerous complications such as hysterectomy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%